Brainstroming and teambuilding workshop, department of surgery, 2024 - Rusli, Siti Mayuha; Abdul Rashid, Nor Faezan; Osman, Nora Julianna; Hassan, Mohd Razin; Yusoff, Ahmad Ramzi; Ahmad Nazlan, Mohd Fadhil; Isahak, Mohamed Izzad; Zainal Abidin, Muhammad Fihmi; Abd Hamid, Mohammad Syamil; Mohamad Shukri, Mohammad Zaki (Faculty of Medicine, 2024)
For the first time ever, on the 14 and 15 of September, the Department of Surgery from the Faculty of Medicine as well as from Hospital Al-Sultan Abdullah (HASA) had organized a brainstorming and team-building workshop in EryabySURIA, Hotspring Bentong, Pahang. There were 26 participants were involved in the workshop.